Genome‐wide microRNA analysis of HPV‐positive self‐samples yields novel triage markers for early detection of cervical cancer. Issue 2 (4th November 2018) - Snoek, Barbara C.; Verlaat, Wina; Babion, Iris; Novianti, Putri W.; van de Wiel, Mark A.; Wilting, Saskia M.; van Trommel, Nienke E.; Bleeker, Maaike C.G.; Massuger, Leon F.A.G.; Melchers, Willem J.G.; Sie, Daoud; Heideman, Daniëlle A.M.; et al.
Abstract : Offering self‐sampling for HPV testing improves the effectiveness of current cervical screening programs by increasing population coverage. Molecular markers directly applicable on self‐samples are needed to stratify HPV‐positive women at risk of cervical cancer (so‐called triage) and to avoid over‐referral and overtreatment. Deregulated microRNAs (miRNAs) have been implicated in the development of cervical cancer, and represent potential triage markers. However, it is unknown whether deregulated miRNA expression is reflected in self‐samples. Our study is the first to establish genome‐wide miRNA profiles in HPV‐positive self‐samples to identify miRNAs that can predict the presence of CIN3 and cervical cancer in self‐samples. Small RNA sequencing (sRNA‐Seq) was conducted to determine genome‐wide miRNA expression profiles in 74 HPV‐positive self‐samples of women with and without cervical precancer (CIN3). The optimal miRNA marker panel for CIN3 detection was determined by GRridge, a penalized method on logistic regression. Six miRNAs were validated by qPCR in 191 independent HPV‐positive self‐samples. Classification of sRNA‐Seq data yielded a 9‐miRNA marker panel with a combined area under the curve (AUC) of 0.89 for CIN3 detection. Validation by qPCR resulted in a combined AUC of 0.78 for CIN3+ detection. Our study shows that deregulated miRNA expression associated with CIN3 and cervical cancer development can be detected by sRNA‐Seq in HPV‐positive self‐samples. Validation by qPCR indicates that miRNA expression analysis offers a promising novel molecular triage strategy for CIN3 and cervical cancer detection applicable to self‐samples. Abstract : What's new? MicroRNAs (miRNAs) are suspected of playing a role in cervical cancer development. They are also potential markers for the identification of human papillomavirus (HPV)‐infected women who are at risk of cervical cancer. Here, using small RNA sequencing of HPV‐positive self‐samples from women with and without cervical precancer (CIN3), the authors identify a miRNA signature consisting of multiple miRNAs that is strongly predictive of CIN3. Validation of this signature by qPCR revealed a good clinical performance for CIN3+ detection. The findings suggest that miRNA analysis is an effective means of CIN3+ prediction in HPV‐positive self‐samples obtained for cervical cancer screening.